2015
DOI: 10.3126/kumj.v13i1.13756
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Medication Adherence Pattern and Factors Affecting the Adherence in Chronic Obstructive Pulmonary Disease

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 57 publications
7
33
0
Order By: Relevance
“…Results reflected that the highest improvement of medication adherence was seen among young adults (18-35 years) compared to middle and older adults; researchers suggested that this may be due to many of subjects in this age group had a high literacy rate helped them to understand the medication instructions versus to poor medication adherence was found in older adults. These findings were on the line with (Shrestha et al, 2015 andShakya et al, 2016) who found that poor adherence to H. pylori medication was higher in old age compared to young adults, and discussed as elderly people may have more than one chronic illness and use multi drugs that can affect their compliance to H pylori treatment, and they can't tolerate the side effects of the treatment course. Moreover, authors of this research viewed that a high rate of illiteracy and forgetfulness are considered other reasons for missing dose among older people.…”
Section: Discussion: -supporting
confidence: 82%
“…Results reflected that the highest improvement of medication adherence was seen among young adults (18-35 years) compared to middle and older adults; researchers suggested that this may be due to many of subjects in this age group had a high literacy rate helped them to understand the medication instructions versus to poor medication adherence was found in older adults. These findings were on the line with (Shrestha et al, 2015 andShakya et al, 2016) who found that poor adherence to H. pylori medication was higher in old age compared to young adults, and discussed as elderly people may have more than one chronic illness and use multi drugs that can affect their compliance to H pylori treatment, and they can't tolerate the side effects of the treatment course. Moreover, authors of this research viewed that a high rate of illiteracy and forgetfulness are considered other reasons for missing dose among older people.…”
Section: Discussion: -supporting
confidence: 82%
“…All these findings are physiologically expected and have been well‐documented in previous studies (Christensen et al, 2016; Ding, Judge, Small, Bent‐Ennakhil, & Siddiqui, 2018; Miravitlles & Ribera, 2017). Increasing age influences medication adherence (Acharya & Sharma, 2019; Krauskopf et al, 2015; Shrestha et al, 2015). In this study, older patients were more adherent to their medications.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Some studies suggest that older age is a risk factor for non-adherence due to factors such as cognitive impairment, particularly forgetfulness and polypharmacy. 54 A recent study carried out in Saudi Arabia, based on the findings from a National household survey, reported that older age was associated with better treatment adherence in subjects with chronic diseases. 5 It has also been reported that patients with poor adherence often have insufficient understanding of their disease and its management options, and tend to rely more on natural remedies, 55 which could be linked to patient education.…”
Section: Discussionmentioning
confidence: 99%